Type 2 diabetes mellitus patients' knowledge, attitude and practice of lifestyle modifications - Paul I. Peter; Wilhelm J. Steinberg; Cornel van Rooyen; Johan Botes (AOSIS, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a significant health burden globally, with uncontrolled DM often resulting in short- and long-term complications. Unfortunately, healthcare providers have little control over patients' necessary lifestyle modification practices outside the consultation room. Aim: To determine the level of knowledge, attitude and practice (KAP) of lifestyle modifications among patients with T2DM attending the National District Hospital Outpatient Department, Bloemfontein, and identify possible barriers to lifestyle modifications experienced by patients. Setting: Outpatient Department at a Free State hospital. Methods: Using a cross-sectional study, patients with previously diagnosed T2DM were invited to participate. Respondents completed a structured questionnaire to assess their KAP regarding lifestyle modifications. Results: Of the 149 respondents, 64.4% (n = 94) were obese and 24.0% (n = 35) overweight despite good knowledge of lifestyle modifications. Respondents displayed a positive attitude toward physical exercise but less so to adjusting their diets. In practice, 63.4% (n = 83) claimed to exercise regularly, but two-thirds irregularly monitored their weight. The practice of a controlled and planned diet was poor. Perceived barriers to lifestyle modifications included being too busy to engage in physical exercise, bad weather and financial constraints. Conclusion: Despite displaying good knowledge regarding lifestyle modifications, the attitude and practice thereof remain poor. It is essential to re-emphasise to patients why it is crucial to engage in lifestyle modification practices and assess whether they are doing so correctly. Contribution: It highlights the importance of lifestyle considerations of T2DM patients in the clinical context.